The fig as a biological product: case of the Taounate Region in Morocco - Abidar A. (The market for organic products in the Mediterranean region, 2003)
This work aims to examine the fig sector in a vast area of the fig production in Morocco (area of Taounate). This area representing 50% of the total national area is regarded as the main center of fig in Morocco with 22000ha. A sample of 140 farmers representing the region were selected and interviewed about their fig production system. The descriptive analysis showed that fig, as it is cultivated fulfils the requirements of biological products. However there are many problems that need to be solved in terms of quality and marketing strategy.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)